آليات تفعيل التوظيف الديداكتيكي في المادة الدراسيةمن اجل تفعيل العلاقة بين الطالب والمدرس - يخلف, رفيقة (Changement Social, 2019)
هناك العديد من الدراسات النفسية والاجتماعية تناولت عدة قضايا التي تمس المؤسسة التربوية  والتطرق إلى المشاكل التي تعاني منها مثل مشكل العنف المدرسي والتسرب وأنماط التفاعل التربوي، والعلاقات والاتصال التربوي...الخ، لكن هناك عنصر مهم في هذا المجال إذا تحدثنا عن كيفية تفعيل العلاقة بين المدرس و الطالب، وهذا العنصر يمثل المادة التدريسية التي تعتبر إحدى ركائز العقد الدياكتيكي في العملية التعليمية، لكن المعرفة التدريسية لها خصائص وأهداف وبرامج واستراتيجيات يجب معرفتها لكي تصل إلى الطالب، وتفاعل الطالب مع المادة الدراسية هو تفاعل مع المدرس، وهذا ما يطلق عليه مصطلح ديداكتيك المادة التدريسية، لذا نحاول من خلال هذه الدراسة معرفة آليات التفعيل  التوظيف الديداكتيكي  في المادة الدراسية من اجل  تفعيل العلاقة بين الطالب والمدرس، ولذا سنتبع الخطوات التالية: -ماهية الديداكتيك. - آليات توظيف ديداكتيكي في المادة التدريسيبة. - أهمية تطبيق استراتيجيات ديداكتيك المادة التدريسية في تفعيل العلاقة بين المدرس والطالب. الكلمات المفتاحية: التوظيف الدياكتيكي، تفعيل العلاقة ومن هذا المنطلق تكمن إشكاليتنا البحثية في مدى تطبيقية هذا العلم بآليته المنهجية والفكرية في فهم واقعناالعربي. There are Researchs  psychological and social studies dealt with several issues that affect the educational institution and address the problems that suffer, such as the problem of school violence and dropout and patterns of educational interaction, relations and educational communication, etc., but there is an important element in this area if We talked about how to activate the relationship between the teacher and the student, and this component represents the teaching material, which is one of the pillars of the contract in the process of education, but teaching knowledge has characteristics, objectives, programs and strategies must be known to reach the student, and the interaction of the student with the subject is Interaction with the teacher This is called the term didactic teaching material, so we are trying through this study knowledge of activation of employment mechanisms Aldisdakteka in the course material in order to activate the relationship between the student and the teacher, and so we will follow these steps: - the Didactic Definition of-Subject  -the Didactic in student  Methods of employment - The importance of Apply strategies the Didactic strategies in student subject in activating the relationship between teacher and student.. Keywords : Deactivating Employment, Relationship Activation. the status of anthropology in the world.